2020
DOI: 10.1088/1475-7516/2020/04/019
|View full text |Cite
|
Sign up to set email alerts
|

Baryonic effects for weak lensing. Part I. Power spectrum and covariance matrix

Abstract: Baryonic feedback effects lead to a suppression of the weak lensing angular power spectrum on small scales. The poorly constrained shape and amplitude of this suppression is an important source of uncertainties for upcoming cosmological weak-lensing surveys such as Euclid or LSST. In this first paper in a series of two, we use simulations to build a Euclidlike tomographic mock data-set for the cosmic shear power spectrum and the corresponding covariance matrix, which are both corrected for baryons following th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 73 publications
3
74
0
Order By: Relevance
“…This was shown to be a good approximation in van Daalen et al ( 2020) by running hydro-simulations given the span of cosmology from WMAP 2009 (Hinshaw et al 2013) to Planck 2015 (Planck Collaboration et al 2016). Schneider et al (2020) also showed that ignoring the coupling between baryon and cosmology would be valid for future stage IV weak lensing experiments. We adopt the fiducial flat-ΛCDM cosmology shown in Table 1.…”
Section: Modelling the Theoretical Error Covariancementioning
confidence: 93%
“…This was shown to be a good approximation in van Daalen et al ( 2020) by running hydro-simulations given the span of cosmology from WMAP 2009 (Hinshaw et al 2013) to Planck 2015 (Planck Collaboration et al 2016). Schneider et al (2020) also showed that ignoring the coupling between baryon and cosmology would be valid for future stage IV weak lensing experiments. We adopt the fiducial flat-ΛCDM cosmology shown in Table 1.…”
Section: Modelling the Theoretical Error Covariancementioning
confidence: 93%
“…Although improving the gravity-only predictions on small scales will be an important task, baryons have a much more important impact on these scales and thus for the overall accuracy of the predictions. To address this, also emulators have been built based on physically-motivated models for baryonic effects, which claim that they can also obtain few percent accuracy (Schneider et al 2020;Arico `et al 2021a). Although they are close to the target accuracy, they are likely only sufficient for the first round of data analysis of upcoming surveys, but continued improvement in precision will be needed.…”
Section: Challenges For Cosmological Predictionsmentioning
confidence: 99%
“…Systematic effects can be mitigated by excluding the small scales (k 10 −1 h/Mpc) when fitting the measured power spectra, although that comes at the price of greatly increased uncertainties in the resulting cosmological parameters. Constraints on extended cosmologies, such as massive neutrinos, variable dark energy equation of state, or chameleon gravity, require sensitivity on smaller scales, and their effect is strongly degenerate with that of baryonic physics [326,327].…”
Section: Impact On Cosmological Probesmentioning
confidence: 99%